2006
DOI: 10.1194/jlr.m500473-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Lipids isolated from bone induce the migration of human breast cancer cells

Abstract: Bone is the most common site to which breast cancer cells metastasize. We found that osteoblast-like MG63 cells and human bone tissue contain the bile acid salt sodium deoxycholate (DC). MG63 cells take up and accumulate DC from the medium, suggesting that the bone-derived DC originates from serum. DC released from MG63 cells or bone tissue promotes cell survival and induces the migration of metastatic human breast cancer MDA-MB-231 cells. The bile acid receptor farnesoid X receptor (FXR) antagonist Z-guggulst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 48 publications
4
55
4
Order By: Relevance
“…The nuclear receptor FXR has been recently demonstrated in breast cancer as well as in normal mammary tissue [13][14][15]. The present study reveals a higher FXR expression in ER-positive luminal-like tumors, as compared to ER-negative breast tumors.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The nuclear receptor FXR has been recently demonstrated in breast cancer as well as in normal mammary tissue [13][14][15]. The present study reveals a higher FXR expression in ER-positive luminal-like tumors, as compared to ER-negative breast tumors.…”
Section: Discussionsupporting
confidence: 65%
“…Surprisingly, we and others have also found FXR expression in breast cancer tissue and breast cancer cell lines [13][14][15]. With regard to breast cancer development, the presence of high plasma levels of deoxycholic acid in postmenopausal breast cancer patients, as compared to healthy controls matched for age and body mass index, has been documented, suggesting that this bile acid might be involved in mammary gland carcinogenesis [16].…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Data from this assay was consistent with the transwell assay; while significant migration could be observed over the 24 hour incubation period, there was no significant increase when MCF-7 or MDA-MB-231 cells were exposed to FXR agonists (Figure 7b). This data appears in conflict with that of Silva et al, who demonstrated that the secondary bile acid deoxycholate could induce migration of MDA-MB-231, but not MCF-7 cells [48].…”
Section: 4! Activation Of Fxr In Breast Cancer Cell Lines Does Notcontrasting
confidence: 56%
“…Structural diversity of each lipid or lipid class will have a distinct effect on membrane properties (i.e., fluidity, permeability, oxygen scavenging, etc.). [4][5][6][7][8][9][10][11][12][13][14][15] Therefore, the potential advantage of the combined use of HPLC, MS, and NMR spectroscopy should be explored. Many studies have explored the analysis of lipids, but to our knowledge a combinatorial approach has rarely been used.…”
mentioning
confidence: 99%